2018
DOI: 10.1038/s41612-018-0038-4
|View full text |Cite
|
Sign up to set email alerts
|

A signal-to-noise paradox in climate science

Abstract: We review the growing evidence for a widespread inconsistency between the low strength of predictable signals in climate models and the relatively high level of agreement they exhibit with observed variability of the atmospheric circulation. This discrepancy is particularly evident in the climate variability of the Atlantic sector, where ensemble predictions using climate models generally show higher correlation with observed variability than with their own simulations, and higher correlations with observation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

29
328
1
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 293 publications
(359 citation statements)
references
References 98 publications
(177 reference statements)
29
328
1
1
Order By: Relevance
“…We have confirmed that the predictions of both of these signal/noise models are in good agreement with hindcasts that have been verified against a reanalysis. All of these results provide evidence of tropospheric predictability on S2S timescales during spring and summer from at least as early as 1 August and show no evidence of a signal‐to‐noise paradox between the hindcasts and the reanalysis (Scaife & Smith, ). We note that it may be the case that tropospheric predictability is larger in years with a more severe shift of the stratospheric seasonal cycle, with the SSW of 2002 perhaps the most extreme example of such behavior (see Thompson et al, , for a discussion of tropospheric impacts associated with the SSW of 2002.…”
Section: Summary and Discussionmentioning
confidence: 71%
See 2 more Smart Citations
“…We have confirmed that the predictions of both of these signal/noise models are in good agreement with hindcasts that have been verified against a reanalysis. All of these results provide evidence of tropospheric predictability on S2S timescales during spring and summer from at least as early as 1 August and show no evidence of a signal‐to‐noise paradox between the hindcasts and the reanalysis (Scaife & Smith, ). We note that it may be the case that tropospheric predictability is larger in years with a more severe shift of the stratospheric seasonal cycle, with the SSW of 2002 perhaps the most extreme example of such behavior (see Thompson et al, , for a discussion of tropospheric impacts associated with the SSW of 2002.…”
Section: Summary and Discussionmentioning
confidence: 71%
“…More specifically, it allows for a continuous rather than a discrete representation of the signal. A potential disadvantage of this alternative signal‐to‐noise model is that recent work has suggested that some forecast models used in numerical weather prediction may be overdispersive (Scaife & Smith, ; but see also Weisheimer et al, ; Osman et al, ). If such an overdispersive scenario was the case for the present hindcast ensemble, then this alternative signal‐to‐noise model would offer an unduly pessimistic estimate of S2S forecast skill.…”
Section: S2s Hindcasts Of the Extratropical Circulationmentioning
confidence: 99%
See 1 more Smart Citation
“…() demonstrate, using a set of perturbation experiments, that the pattern of north Atlantic SSTs in May 2018 (and compared to 1976 in Figure ), sometimes referred to as the north Atlantic tripole pattern, correlates with northern European rainfall through the process of a northward‐shifted jet stream responding to the meridional temperature gradient of the north Atlantic sector. They go on to note that, although the North Atlantic SST tripole likely contributed to the observed circulation changes of summers, such as 1976 and 2018, the model produced only a very weak signal, which is often found in predictions of north Atlantic atmospheric variability (Scaife and Smith, ). In addition, the world has warmed significantly since the 1970s, and this is also partly reflected in the comparison of 2018 and 1976 in Figure .…”
Section: The Atlantic Sea‐surface Temperature (Sst) Tripolementioning
confidence: 97%
“…Comparisons of observations and model simulations in the North Atlantic in terms of the mean state, total and decadal-scale variance, empirical orthogonal function and Atlantic multidecadal variability patterns ( Figures S1-S4) indicate that SST variability is underestimated in CCSM4, especially in the subtropics. This underestimate is possibly due to the underestimate of ocean-atmosphere interactions (Scaife & Smith, 2018) and the unresolved ocean eddy activities . The North Atlantic multimodel studies suggest that models differ greatly in the timescale, structure, and relation of ocean and atmospheric variability (Ba et al, 2014;Kavvada et al, 2013), which could lead to different estimates of predictability (Branstator et al, 2012).…”
Section: Decadal Sst Predictabilitymentioning
confidence: 99%